Patterns of Otorhinolaryngological Disorders in Subjects with Diabetes - ZJ, Gazzaz; MN, Makhdom; KO, Dhafar; O, Maimini; MU, Farooq; A, Rasheed (IIUM Medical Journal Malaysia, 2011)
Objective: To find out the prevalence of otorhinolaryngological disorders in patients with diabetes mellitus who presented to Ear, Nose and Throat (ENT) clinic at Al-Noor specialist hospital, Makkah, Saudi Arabia. Materials & Methods: This observational retrospective study was carried out over a period of one year, from July 15, 2004 to July 20, 2005 by the collaboration of ENT Department and Health Research Center of Al-Noor Specialist Hospital, Makkah, Saudi Arabia. Patients’ information was collected such as the demography, types and durations of diabetes, types of diabetic treatments, and fi nal ENT diagnosis. Subjects’ random blood sugar and hemoglobin A1c (HbA1c) levels were collected on the fi rst visit to the ENT-Outpatient Department. Results: One hundred patients met the inclusion criteria; with mean age of 51.5 years (age range 14-86 years). Thirty-nine percent of the patients were at the age of 45-54 years old. Males (52%) slightly out-numbered the females. Majority had diabetes mellitus type 2 and 78% patients had high HbA1c levels indicating poor glycemic controls. The most common ENT disorder was rhinitis (19%), followed by sensorineural hearing loss (12%) and malignant otitis externa (8%). Conclusion: The most common ENT disorder in patients with diabetes mellitus type 2 was rhinitis, followed by sensorineural hearing loss. Majority of these patients had poor glycemic control, hence can explain the predominance of certain disorders over others.